2016
DOI: 10.1039/c6ra19784a
|View full text |Cite
|
Sign up to set email alerts
|

Soluble silicon patterns and templates: calcium phosphate nanocrystal deposition in collagen type 1

Abstract: OSA interactsviaionic cross-linking to collagen molecules; free hydroxyl ions recruit CaP nano-precursors and aid nucleation within the fibrils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Raman spectroscopy showed suppression of a secondary alcohol vibration, with a reduction in the C–O bond peak, between 0 and 200 ppm collagen samples. This suggests that cobalt ions interact specifically with a hydroxyl group. Although this is present within the hydroxyproline, previous studies into complex interactions with collagens show preferential binding to terminal sites of the molecule . Therefore, it is more likely that the cobalt ions interact with the hydroxyl structure at the carboxylic terminal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Raman spectroscopy showed suppression of a secondary alcohol vibration, with a reduction in the C–O bond peak, between 0 and 200 ppm collagen samples. This suggests that cobalt ions interact specifically with a hydroxyl group. Although this is present within the hydroxyproline, previous studies into complex interactions with collagens show preferential binding to terminal sites of the molecule . Therefore, it is more likely that the cobalt ions interact with the hydroxyl structure at the carboxylic terminal.…”
Section: Discussionmentioning
confidence: 99%
“… 52 54 Although this is present within the hydroxyproline, previous studies into complex interactions with collagens show preferential binding to terminal sites of the molecule. 55 Therefore, it is more likely that the cobalt ions interact with the hydroxyl structure at the carboxylic terminal. DSC measurements showed that a 14% decrease in energy is required to remove bound water from the 200 ppm CoCol gel.…”
Section: Discussionmentioning
confidence: 99%
“…In this field, the mechanism of HAP’s deposition in collagen and silicon-related collagen mineralization are the focus. In view of the fact that silicon accounts for 0.5 wt % of newly formed bone and that the lack of silicon will lead to skeletal deformity, scientists have long found the important role of silicon in paleontology or collagen mineralization. Recently, silicon-related collagen mineralization has shown important progress. For example, silicon-reinforced collagen can be used as a template for more orderly deposition of HAP .…”
Section: Biomineralization Foundation Of Hard Tissuesmentioning
confidence: 99%